Clinical covariates that improve surgical risk prediction and guide targeted prehabilitation: an exploratory, retrospective cohort study of major colorectal cancer surgery patients evaluated with preoperative cardiopulmonary exercise testing - Vladimir Bolshinsky; Hilmy Ismail; Michael Li; Jarrod Basto; Robert Schier; Anna Hagemeier; Kwok-Ming Ho; Alexander Heriot; Bernhard Riedel (Perioperative Medicine, 2022)
Abstract Background Preoperative risk stratification is used to derive an optimal treatment plan for patients requiring cancer surgery. Patients with reversible risk factors are candidates for prehabilitation programmes. This pilot study explores the impact of preoperative covariates of comorbid disease (Charlson Co-morbidity Index), preoperative serum biomarkers, and traditional cardiopulmonary exercise testing (CPET)-derived parameters of functional capacity on postoperative outcomes after major colorectal cancer surgery. Methods Consecutive patients who underwent CPET prior to colorectal cancer surgery over a 2-year period were identified and a minimum of 2-year postoperative follow-up was performed. Postoperative assessment included: Clavien-Dindo complication score, Comprehensive Complication Index, Days at Home within 90 days (DAH-90) after surgery, and overall survival. Results The Charlson Co-morbidity Index did not discriminate postoperative complications, or overall survival. In contrast, low preoperative haemoglobin, low albumin, or high neutrophil count were associated with postoperative complications and reduced overall survival. CPET-derived parameters predictive of postoperative complications, DAH-90, and reduced overall survival included measures of VCO2 kinetics at anaerobic threshold (AT), peakVO2 (corrected to body surface area), and VO2 kinetics during the post-exercise recovery phase. Inflammatory parameters and CO2 kinetics added significant predictive value to peakVO2 within bi-variable models for postoperative complications and overall survival (P < 0.0001). Conclusion Consideration of modifiable ‘triple low’ preoperative risk (anaemia, malnutrition, deconditioning) factors and inflammation will improve surgical risk prediction and guide prehabilitation. Gas exchange parameters that focus on VCO2 kinetics at AT and correcting peakVO2 to body surface area (rather than absolute weight) may improve CPET-derived preoperative risk assessment.